A study on the effects of college students’ knowledge-sharing behavior on group performance and individual social status - Li Jia; Zhikun Liang; Chuanping Lei; Li Huang (Frontiers in Psychology, 2023)
IntroductionUniversities, as typical knowledge-based organizations, engage in various knowledge management activities, including knowledge acquisition, storage, application, and innovation. This research focuses on applying organizational knowledge management principles to college student groups in universities, aiming to explore the current state of knowledge-sharing behaviors within these groups and investigate the relationship between group performance, individual social status, and knowledge-sharing behaviors.MethodsA sample of 497 college students from six universities in China was randomly selected, and an econometric analysis using structural equation modeling was conducted with SPSS21.0 and AMOS21.0 to examine their knowledge-sharing behaviors, individual social status, and group performance.ResultsThe findings reveal that individual knowledge-sharing behavior significantly influences the knowledge sharing behavior of others and the recognition received by the sharer. Moreover, the knowledge-sharing behavior of others positively contributes to group performance, while recognition from others enhances the social status of the sharer. Furthermore, the knowledge-sharing behaviors of others mediate the relationship between individual knowledge-sharing behaviors and group performance, while others’ recognition of the sharer mediates the relationship between individual knowledge-sharing behaviors and the sharer’s social status. This study provides valuable theoretical guidance for organizational knowledge management and the development of college students’ learning abilities, establishing a crucial foundation for comprehensive, scientific, and standardized student management.ConclusionOverall, this research contributes to understanding the dynamics of knowledge sharing among college students and highlights the importance of incorporating knowledge management principles in educational settings. The findings underscore the positive impact of knowledge sharing on group performance and individual social status, emphasizing the need for effective knowledge sharing practices to enhance student management in higher education institutions.